2017
DOI: 10.4103/0972-2327.199903
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between hippocampal volumes and medial temporal lobe atrophy in patients with Alzheimer's disease

Abstract: Introduction:Hippocampus undergoes atrophy in patients with Alzheimer's disease (AD). Calculation of hippocampal volumes can be done by a variety of methods using T1-weighted images of magnetic resonance imaging (MRI) of the brain. Medial temporal lobes atrophy (MTL) can be rated visually using T1-weighted MRI brain images. The present study was done to see if any correlation existed between hippocampal volumes and visual rating scores of the MTL using Scheltens Visual Rating Method.Materials and Methods:We sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…In line with previous studies mostly performed in late-onset cognitive impairment, we observed a moderate correlation between MTA visual rating and volumetric techniques (Dhikav et al, 2017). The moderate correlation could be explained because MTA score is based mostly on a single slice while HV is a three-dimensional measure.…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous studies mostly performed in late-onset cognitive impairment, we observed a moderate correlation between MTA visual rating and volumetric techniques (Dhikav et al, 2017). The moderate correlation could be explained because MTA score is based mostly on a single slice while HV is a three-dimensional measure.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that pathological changes in the olfactory cortex of the hippocampus appear in the early stages of AD, and hippocampal atrophy is believed to be a sensitive marker for diagnosis of AD. 21 The baseline hippocampal volume of patients with AD was positively correlated with MMSE score in a previous study, 22 which was consistent with the results of the present study. Left hippocampal volume, right hippocampal volume, and total hippocampal volume were all decreased in patients with AD compared with those in healthy controls, and these decreases in volume correlated with decreased MMSE score.…”
Section: Discussionsupporting
confidence: 92%
“…Studies have indicated that cardiovascular factors (e.g. hypertension or/and diabetes, coronary artery disease, cerebrovascular accidents, arterial disease, etc) affect the development of cognition [1][2][3][4][5][6]. A recent study [7] with more than 400 participants confirmed that the presence of cardiovascular risk factors impacts mild cognitive impairment development, which is detectable in the primary care setting.…”
Section: Association Between Cardiovascular Comorbiditiesmentioning
confidence: 99%
“…Cardiovascular diseases are known to contribute to cognitive decline [1][2][3][4][5][6], but it is unclear whether the reverse is also true. It is clear that hypertension or/and diabetes are common cardiovascular conditions leading to changes in brain structure and function.…”
Section: Introductionmentioning
confidence: 99%